Pengetahuan Ibu Menyusui Tentang Asi Ekslusif Di Desa Rambah Samo Kecamatan Rambah Samo I Kabupaten Rokan Hulu - Lilis Simanungkalit, Eka Yuli Handayani, (Jurnal Martenity and Neonatal, 2013)
Breast milk nutrients needed in the process of growth and development of infants . Exclusive breastfeeding is the only breast-fed infants without additional other liquids , and without the addition of other foods fed to infants until the age of 6 months . Mother's Milk based on data from the Department of Health Rokan Hulu Exclusively breastfed infants are most 48.6 % in the lowest number of health centers as much as 22.2 % Rambah samo . The purpose of this study was to determine the knowledge of nursing mothers on exclusive breastfeeding in the browse samo village . The method used is descriptive research design using cross-sectional approach . How sampling with purposive sampling . The data was collected using primary data obtained by distributing questionnaires as much as 66 nursing mothers . The results of investigations in this is that the level of knowledge of exclusive breastfeeding Breastfeeding On Rambah Samo In the village is a good mother who is knowledgeable as many as 14 people (21.2 %) , Just 35 (53 %) , and less is 17 people (25.8 %) . The conclusion of the study is the knowledge of nursing mothers on exclusive breastfeeding mother who is knowledgeable enough , as many as 35 people ( 53.0 % ) . After doing research , the researcher hopes to provide a source of information about exclusive breastfeeding by providing counseling or health education to nursing mothers , so mothers understand the importance of exclusive breastfeeding for infants.